Epidemiology of Pediatric Brain Tumor in the Center of Referral Hospital in North Sumatera from 2013 -2017 - Putra, Prawira; Tala, Ihsan Z; Dharmajaya, Ridha; Mouza, Abdurrahman; Tandean, Steven (Talenta Universitas Sumatera Utara, 2019)
Brain tumors are the most common disease group of solid tumors in childhood, and children with brain tumors have a relatively poor survival rate. Epidemiologic data from a hospital-based registry provide the necessary information to obtain a full picture of the frequency of this disease, which is a great challenge in pediatric oncology. One hundred thirty four tumors in children between 0 and 17 years of age diagnosed between 2013 to 2017 were classified according the sex, and topography. Incidence of brain tumor in boys were higher than girls. From the registry data, the prevalence for boys was higher (67%). In the whole series, 54% were supratentorial, 46% infratentorial. The most common histopathologic pattern seen in the registry were pilocytic astrocytoma which accounts for 42 cases (31%) followed by medulloblastoma and craniopharygioma with the percentage of 25% and 18% respectively. The least histopathologic pattern of pediatric tumor seen in our center are diffuse astrocytoma and choroid plexus papiloma which was only seen in 1 patient for the last 5 years of our experience.